Momentum considerations on the New MEXICO experiment. Issue 7 (September 2016) - Parra, E A; Boorsma, K; Schepers, J G; Snel, H
Abstract: The present paper regards axial and angular momentum considerations combining detailed loads from pressure sensors and the flow field mapped with particle image velocimetry (PIV) techniques. For this end, the study implements important results leaning on experimental data from wind tunnel measurements of the New MEXICO project. The measurements, taken on a fully instrumented rotor, were carried out in the German Dutch Wind tunnel Organisation (DNW) testing the MEXICO rotor in the open section. The work revisits the so-called momentum theory, showing that the integral thrust and torque measured on the rotor correspond with an extent of 0.7 and 2.4% respectively to the momentum balance of the global flow field using the general momentum equations. Likewise, the sectional forces combined with the local induced velocities are found to plausibly obey the annular streamtube theory, albeit some limitations in the axial momentum become more apparent at high inductions after a=0.3. Finally, azimuth induced velocities are measured and compared to predictions from models of Glauert and Burton et al., showing close-matching forecasts for blade spans above 25%.